Introduction geographic information system - Chang, Kang-Tsung (New York : McGraw-Hill, 2012)
Provides students in a first or second GIS course with a foundation in both GIS concepts and the use of GIS. This title presents GIS terms and concepts and helps students learn how each one fits into a complete GIS system
1 Introduction -- 2 Coordinate systems -- 3 Vector data model -- 4 Raster data mod -- 5 GIS data acquisition -- 6 Geometric transformation -- 7 Spatial data accuracy and quality -- 8 Attribute data management -- 9 Data display and cartography -- 10 Data exploration -- 11 Vector data analysis -- 12 raster data analysis -- 13 Terrain mapping and analysis -- 14 View sheds and watershed -- 15 Spatial interpolation -- 16 Geocoding and dynamic segmentation -- 17 Least cost path and network analysis -- 18 GIS models and modeling
Includes bibliographical references and index
Keywords: Geographic information systems